Fenofibrate as an Adjunct Therapy for Ulcerative Colitis: Targeting Inflammation via SIRT1, NLRP3, and AMPK Pathways: A Randomized Controlled Pilot Study - Alarfaj SJ; Bahaa MM; Elmasry TA; Elberri EI; El-Khateeb E; Hamouda AO; Salahuddin MM; Kamal M; Gadallah ANAA; Eltantawy N; Yasser M; Negm WA; et al. (Dove Medical Press, 2024)
Sumaiah J Alarfaj,1 Mostafa M Bahaa,2 Thanaa A Elmasry,3 Eman I Elberri,4 Eman El-Khateeb,4 Amir O Hamouda,5 Muhammed M Salahuddin,5 Marwa Kamal,6 Abdel-Naser Abdel-Atty Gadallah,7 Nashwa Eltantawy,8 Mohamed Yasser,9- 11 Walaa A Negm,12 Manal A Hamouda,13 Amsha S Alsegiani,14 Sarah Alrubia,14 Mamdouh Eldesoqui,15 Mahmoud S Abdallah16,17 1Department of Pharmacy Practice, College of Pharmacy, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 2Pharmacy Practice Department, Faculty of Pharmacy, Horus University, New Damietta, Egypt; 3Pharmacology and Toxicology Department, Faculty of Pharmacy, Tanta University, Tanta, Egypt; 4Clinical Pharmacy Department, Faculty of Pharmacy, Tanta University, Tanta, Egypt; 5Department of Biochemistry and Pharmacology, Faculty of Pharmacy, Horus University, New Damietta, Egypt; 6Department of Clinical Pharmacy, Faculty of Pharmacy, Fayoum University, Fayoum, Egypt; 7Internal Medicine Department, Faculty of Medicine, Menofia University, Menofia, Egypt; 8Department of Pharmacy Practice, Faculty of Pharmacy and Drug Technology, Egyptian Chinese University, Cairo, Egypt; 9Department of Pharmaceutics, Faculty of Pharmacy, Port Said University, Port Said, Egypt; 10Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Horus University, New Damietta, Egypt; 11Department of Pharmaceutics, Faculty of Pharmacy, East Port Said National University, Port Said, Egypt; 12Pharmacognosy Department, Faculty of Pharmacy, Tanta University, Tanta, Egypt; 13Department of Clinical Pharmacy, Faculty of Pharmacy, Menofia University, Menofia, Egypt; 14Pharmaceutical Chemistry Department, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 15Department of Basic Medical Sciences, College of Medicine, AlMaarefa University, Riyadh, Saudi Arabia; 16Department of Clinical Pharmacy, Faculty of Pharmacy, University of Sadat City (USC), Sadat City, Menoufia, Egypt; 17Department of PharmD, Faculty of Pharmacy, Jadara University, Irbid, JordanCorrespondence: Mostafa M Bahaa, Pharmacy Practice Department, Faculty of Pharmacy, Horus University, New Damietta, 34517, Egypt, Tel +0201025538337, Email mbahaa@horus.edu.egBackground: Ulcerative colitis (UC) is an idiopathic chronic inflammation of colonic and rectal mucosa. The peroxisome proliferator-activated receptor α (PPARα) has been identified as having protective effects in UC.Aim: The study aimed to investigate the efficacy of fenofibrate, a PPARα agonist, in UC.Methods: A total of 70 patients with mild to moderate UC were allocated randomly and assigned to two groups (n = 35 each) from Gastroenterology Department, Faculty of Medicine, Menoufia University. The mesalamine group received a placebo along with 1 g of mesalamine three times daily, while the fenofibrate group received 1 g of mesalamine three times and fenofibrate 160 mg once daily. The study duration was for six months. A gastroenterologist assessed patients by non-invasive Partial Mayo Score (PMS) and the Inflammatory Bowel Disease Questionnaire (IBDQ) to evaluate clinical response and remission. The serum levels of silent information regulator 1 (SIRT1), NOD-like receptor protein 3 (NLRP3), and adenosine monophosphate activated protein kinase (AMPK), as well as fecal calprotectin levels were examined to determine the biological effect of fenofibrate.Results: After treatment, the fenofibrate group showed statistically significant reductions in PMS (p = 0.044) and improved digestive domain of IBDQ (p = 0.023). Additionally, there were significant decreases in serum NLRP3 (p = 0.041) and fecal calprotectin (p = 0.035), along with significant increases in SIRT1 (p = 0.002) and AMPK (p = 0.0003). The fenofibrate group also had higher response and remission rates compared to the mesalamine group.Conclusion: Fenofibrate may be a promising adjunct for improving clinical outcomes, quality of life, and modulating inflammation in mild to moderate patients with UC.Trial Registration Identifier: NCT05781698.Keywords: Ulcerative colitis, Fenofibrate, Mesalamine, NLRP3/AMPK, PPAR&#x03B1